Evaluation of agricultural water demand under future climate change scenarios in the Loess Plateau of Northern Shaanxi, China. (January 2018) - Sun, S.K.; Li, C.; Wu, P.T.; Zhao, X.N.; Wang, Y.B.
Highlights: Future Climate (2020–2049) was predicted in Loess Plateau of northern Shaanxi, China. Loess Plateau of northern Shaanxi will have a warmer and humid climate in future. Future climate change scenario was used to predict irrigation water requirement(IWR). IWR of the main crops decreased under future climate change scenarios. Abstract: Climate change will affect the future availability of water resources for agriculture. An understanding of the impact of future climate change on regional agricultural water use can provide a basis for regional agricultural production and water management. This paper evaluated the agricultural water demand under three future climate change scenarios in the Loess Plateau of northern Shaanxi (LPNS), China. The results showed that in the scenarios RCP2.6, RCP4.5, and RCP8.5, the temperature, effective precipitation, and relative humidity were on the rise, the wind speed decreased slightly, and the trend of sunshine duration was unclear. The irrigation water requirements of the main crops exhibited a downward trend under future climate change scenarios. The decreasing trend of the irrigation water requirement was highest in the RCP8.5 (−0.90%) scenario, followed by the RCP4.5 (−0.77%/year) and the RCP2.6 (−0.30%/year) scenarios. Based on the impact of the changes in the evapotranspiration of future crops and the effective precipitation in the RCP2.6 scenario, the irrigation water requirements of the agricultural industry showed a downward trend and decreased from 1.84 × 10 9  m 3 /year (2010–2014 average) to 1.29 × 10 9  m 3 /year (2040–2049 average); the irrigation water requirements of the agricultural industry showed a significant downward trend (P < 0.05) in the RCP4.5 and RCP8.5 scenarios, decreasing from 1.84 × 10 9  m 3 /year (2010–2014 average) to 1.20 × 10 9  m 3 /year (2040–2049 average) and 1.15 × 10 9  m 3 /year (2040–2049 average), respectively. Future research should be aimed at improving the regional climate downscaling and developing a better understanding of the responses of agriculture to regional climate change.